Heave response of a floating vertical cylinder with built-in tuned mass damper - Adi Kurniawan (2008)
This study investigates the feasibility of TMD to reduce the heave response of a freely floating vertical circular cylinder. The TMD is designed and positioned inside the cylinder without significantly altering the hydrostatic stability of the structure. A combination of theoretical, experimental, and numerical studies is employed in the investigation. A preliminary study is first conducted by simplifying the problem into a 2-DOF problem, assuming the added mass and radiation damping as constants. The full linear diffraction and radiation of water waves by the floating cylinder under harmonic wave loadings is then solved semi-analytically, utilising the eigenfunction expansion method, to obtain the hydrodynamic forces and hence, the heave response of the cylinder.